A Comparison of Optimal Tariffs and Welfare under No Lobbying, Domestic Lobbying and Domestic‐foreign Lobbying. (January 2015) - Huang, Xianhai; Jiang, Mobing; Li, Jie
Abstract Whether and what type of the lobbying‐induced trade policies can improve the domestic welfare? We show that as compared to the case of no lobbying and the case of domestic lobbying, the domestic‐foreign lobbying may achieve the lowest tariff and may also realise the highest welfare for the domestic country. Our finding provides a theoretical explanation to the prevalent lobbying competition between Asian firms and US firms in USA recently. We argue that the domestic‐foreign lobbying may contribute to a freer trade in the domestic country, and lobbying competition may be one of the strongest forces pushing for trade liberalisation.